PPE / PPS composition and preparation method thereof

By employing specific formulations and preparation processes, the contradiction between flowability and heat resistance in PPE/PPS compositions at high filler levels has been resolved, achieving a simultaneous improvement in high flowability, high heat resistance, and high dimensional stability. This makes the product suitable for high-performance applications such as 5G mobile phone mid-frames, millimeter-wave radar radomes, and heat dissipation covers for IGBT modules in new energy vehicles.

CN121006053APending Publication Date: 2025-11-25ORINKO ADVANCED PLASTICS CO LTD

Patent Information

Application Number
CN202511389369.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing PPE/PPS compositions exhibit a sharp increase in melt viscosity at high filler levels, leading to problems such as difficulty in thin-wall injection molding, uneven orientation shrinkage, and warping. They cannot simultaneously meet the requirements for high fluidity, high heat resistance, and high dimensional stability.

Method used

A specific formulation design, including PPE resin, PPS resin, glass fiber, inorganic filler, compatibilizer, and flow improver, is used to prepare PPE/PPS compositions via a twin-screw extruder. The three-dimensional synergistic effect of flat glass fiber, flaky mica, and needle-like wollastonite, combined with the dual effects of interfacial lubricant and compatibilizer, enhances melt flowability and dimensional stability.

Benefits of technology

It achieves a balance between high fluidity, high heat resistance and high dimensional stability, significantly improving the material's molding capacity and the structural integrity of the product, meeting the high-temperature service requirements of new energy vehicles and 5G communication components, and ensuring the precision and reliability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a PPE / PPS (polyphenylene sulfide) composition and a preparation method thereof. The composition is prepared from the following components in percentage by weight: 35-45% of PPE resin, 20-30% of PPS resin, 15-30% of glass fiber, 2-15% of inorganic filler, 1-5% of compatilizer, 2-10% of fluidity improver and 0.6-1.5% of other auxiliaries. According to the invention, the contradiction between high flowability and high heat resistance as well as high rigidity and low warpage generally faced by high-filling engineering plastics is solved, and the high-filling engineering plastics are very suitable for the frontier fields with extremely high performance requirements, such as 5G mobile phone middle frames, millimeter wave radar radomes, new energy automobile IGBT module heat dissipation cover plates and the like, and have wide market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to PPE / PPS compositions and their preparation methods. Background Technology

[0002] Polyphenylene oxide (PPE) has garnered significant attention in numerous high-end industrial applications due to its exceptional comprehensive properties, such as inherent high heat resistance, excellent dimensional stability, and superior electrical insulation. However, pure PPE material exhibits extremely high melt viscosity and poor flowability, making it difficult to process efficiently and precisely using conventional injection molding processes. Introducing polystyrene (PS) improves its flowability but reduces its heat resistance, thus failing to meet the stringent requirements of long-term operation at temperatures above 150°C for power electronic devices in new energy vehicles. Polyphenylene sulfide (PPS) resin offers advantages such as high temperature resistance, corrosion resistance, flame retardancy, and good dimensional stability, while the introduction of PPS can reduce melt viscosity. While existing PPE / PPS compositions exhibit excellent heat resistance, their melt viscosity rises sharply at filler contents exceeding 30%, leading to problems such as difficulty in thin-wall injection molding, uneven orientation shrinkage, and post-shrinkage warping. CN118685019A addresses the compatibility and toughness issues of PPE / PPS but does not address the material's dimensional stability and flowability. CN116120747A designs a thermally conductive and highly dimensionally stable PPS material, but its formulation does not solve the problem of a surge in melt viscosity caused by high filler content, nor does it simultaneously achieve both high flowability and high dimensional stability. Summary of the Invention

[0003] In view of this, the present invention provides a PPE / PPS composition and its preparation method to solve the problems mentioned in the background art. It resolves the contradiction between "high flow and high heat resistance" and "high rigidity and low warpage" that high-filled engineering plastics usually face. It is very suitable for cutting-edge fields with extremely high performance requirements, such as 5G mobile phone mid-frames, millimeter-wave radar antenna covers, and heat dissipation covers for IGBT modules in new energy vehicles, and has broad market application prospects.

[0004] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention discloses a PPE / PPS composition prepared from the following components in weight percentages: PPE resin 35-45% PPS resin 20-30% 15-30% glass fiber Inorganic fillers 2-15% Compatibilizer 1-5% Flowability improver 2-10% Other adjuvants: 0.6-1.5%.

[0005] As a further aspect of the present invention: the PPE resin has a melt flow rate of 10-50 g / 10 min at 315°C and 10 kg; and / or, the PPS resin has a melt flow rate of 1000-1200 g / 10 min at 316°C and 5 kg; and / or, the compatibilizer has a melt flow rate of 7-20 g / 10 min at 190°C and 2.16 kg.

[0006] As a further aspect of the present invention: the glass fiber is a flat glass fiber with a cross-sectional length-to-minor axis ratio of 3-5:1.

[0007] As a further aspect of the present invention: the inorganic filler is at least one of mica and wollastonite; the mica is flaky mica with a diameter-to-thickness ratio of 50-120 and an average flake diameter of 10-40 μm; the wollastonite is acicular wollastonite with an aspect ratio of 2-8 and a fiber diameter of 10-30 μm.

[0008] As a further aspect of the present invention: the compatibilizer is a copolymer of styrene and methacrylate.

[0009] As a further aspect of the present invention: the flowability improver is at least one of high-flow polystyrene and hyperbranched polyester-polysiloxane block copolymer.

[0010] As a further aspect of the present invention: the other additives are at least one of lubricants, coupling agents, and antioxidants; And / or, the lubricant is at least one of pentaerythritol tetrastearate, silicone powder, or a mixture thereof; And / or, the coupling agent is γ-aminopropyltriethoxysilane; And / or, the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1 to 1:2.

[0011] Secondly, the present invention discloses a method for preparing the PPE / PPS composition as described above, comprising the following steps: All components except glass fiber are mixed evenly to obtain a mixture; The mixture is added to the main feed port of a twin-screw extruder, and glass fibers are added to the side feed port of the twin-screw extruder. After melting, extrusion, and granulation, a PPE / PPS composition is obtained.

[0012] As a further aspect of the present invention: the temperature of the extruder is 100-200℃ in zone one, 260-300℃ in zone two, 260-320℃ in zone three, 260-320℃ in zone four, 260-320℃ in zone five, 260-320℃ in zone six, 260-320℃ in zone seven, 260-320℃ in zone eight, 260-320℃ in zone nine, 260-320℃ in zone ten, the die temperature is 270-320℃, and the screw speed is 300-700 rpm.

[0013] Thirdly, this invention discloses the application of the above-mentioned PPE / PPS composition in 5G communications, new energy vehicles, precision electronics, millimeter-wave radar, power batteries and ultra-thin-wall injection molded parts.

[0014] Compared with the prior art, the beneficial effects of the present invention are: The PPE / PPS composition prepared by this invention successfully achieves an excellent balance between high fluidity, high heat resistance, and high dimensional stability. Through unique formulation design, its melt flow rate is significantly improved, far exceeding that of conventional high-filler PPE / PPS systems, greatly enhancing the material's mold-filling ability in thin-walled, complex structural parts, and laying a solid foundation for precision injection molding.

[0015] While achieving excellent processing fluidity, the material's key heat resistance properties are not sacrificed. Its heat distortion temperature (HDT) meets the stringent requirements of long-term high-temperature service environments in applications such as new energy vehicle electronics and 5G communication components, ensuring the structural integrity and reliability of the products at high temperatures.

[0016] The PPE / PPS composition prepared by this invention exhibits excellent dimensional stability. Through the three-dimensional synergistic effect of flat glass fibers, sheet-like mica, and needle-like wollastonite, a "sheet-needle-flat" oriented interlocking network is constructed, which effectively suppresses anisotropic shrinkage, enabling the material to maintain a very low coefficient of linear expansion and warpage, thus ensuring the dimensional accuracy and long-term dimensional stability of precision parts.

[0017] HBPSi acts as both an interfacial lubricant and a compatibilizer. During the melt blending process, due to the extremely low surface energy of the polysiloxane segments, HBPSi molecules spontaneously migrate from the matrix resin (PPE / PPS) to the high surface energy filler interface (such as the surface of glass fiber, mica, or wollastonite). The polysiloxane segments form a highly efficient lubricating layer around the filler, significantly reducing friction between fillers and between the filler and the resin matrix. This makes it easier for filler particles to slide and orient in the melt, thereby greatly improving the melt flowability of the entire composite system. The numerous terminal hydroxyl groups (-OH) on the hyperbranched polyester segments can interact with polar groups or other compatibilizers on the filler surface, and may even react with the functional groups at the PPS chain ends, thereby improving interfacial bonding to a certain extent and preventing excessive degradation of mechanical properties due to lubrication. Detailed Implementation

[0018] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0020] The specific information of the raw materials used in the following examples and comparative examples is as follows: PPE resin, manufactured by Nantong Xingchen Synthetic Materials Co., Ltd. PPS resin, manufactured by NHU Co., Ltd. Fiberglass, specifically flat fiberglass, manufactured by Jushi Group; Compatibilizer PS-GMA, manufactured by Jia Yi Rong; The inorganic fillers, flaky mica, are manufactured by Yirui Stone, and wollastonite is manufactured by Jiangxi Aote Technology. Antioxidants, hindered phenolic antioxidants, manufactured by BASF; thioester antioxidants, manufactured by BASF; The flowability improving agent, HBPSi (hyperbranched polyester-polysiloxane block copolymer), is prepared in-house. The preparation method is as follows: HBPSi is obtained by melt polycondensation of AB2 type monomer 2,2-bis(hydroxymethyl)butyric acid and trimethylolpropane (molar ratio 24:1) to obtain hydroxyl-terminated hyperbranched polyester, which is then reacted with terminal epoxy polysiloxane (HBPSi: terminal epoxy polysiloxane molar ratio 1:150) at 80-120℃ and with stannous octoate catalyst at 0.1-0.3 phr to obtain the product.

[0021] Manufacturers of high-flow PS are preferred; All materials are commercially available, commonly used products.

[0022] It is understood that the above-mentioned raw materials and reagents are merely examples of some specific embodiments of the present invention, making the technical solution of the present invention clearer, and do not mean that the present invention can only use the above-mentioned reagents. The specific scope shall be determined by the claims. In addition, unless otherwise specified, "parts" in the examples and comparative examples refer to parts by weight.

[0023] Any range described in this invention includes the endpoint, any value between the endpoints, and any subrange consisting of the endpoint or any value between the endpoints.

[0024] The examples and comparative examples were prepared according to the following methods: Weigh each component according to the proportions in Table 1, and mix all components except for glass fiber (comparative example 3 uses ordinary round glass fiber) evenly to obtain a mixture; The mixture is added to the main feed port of a twin-screw extruder, and glass fibers are added to the side feed port of the twin-screw extruder. The mixture is then melted, extruded, and granulated to obtain a PPE / PPS composition.

[0025] The twin-screw extruder has a length-to-diameter ratio of 40:1, and the temperatures of each zone are set as follows: Zone 1 150℃, Zone 2 280℃, Zone 3 290℃, Zone 4 290℃, Zone 5 290℃, Zone 6 280℃, Zone 7 280℃, Zone 8 280℃, Zone 9 280℃, Zone 10 290℃, and the die head temperature is 290℃. The screw speed is 300 r / min, and the vacuum degree is -0.06 MPa.

[0026] Table 1

[0027] Test case The materials obtained in Examples 1-5 and Comparative Examples 1-5 were subjected to performance tests, and the test results are shown in Table 2. The test items and conditions are as follows: Melt flow rate: Tested according to GB / T 3682-2000 standard, test temperature is 300℃, load is 5kg; Heat distortion temperature: tested according to GB / T 1634; pressure: 1.8 MPa. Coefficient of linear expansion: tested according to GB / T 36800.2-2018 standard; Warpage: Tested according to GB / T 25257-2010 standard, test plate size 100mm*100mm*1mm.

[0028] Table 2

[0029] As shown in Table 2, the formulation provided by this invention has high dimensional stability, such as a low coefficient of linear expansion and low warpage, and has little impact on heat distortion temperature while improving melt flow rate.

[0030] As can be seen from Examples 1, 2, 3 and Comparative Examples 1 and 3-5, the introduction of flat glass fiber, mica and acicular wollastonite can significantly reduce the coefficient of linear expansion and warpage of the material. In Comparative Example 3, when circular glass fibers are used instead of flat glass fibers, the difference between the longitudinal (MD) and transverse (TD) coefficients of linear expansion of the material is large, resulting in reduced dimensional stability. In Comparative Example 4, the absence of flaky mica increased the linear expansion coefficient and warpage of the material. This is because the presence of mica reduces the thermal shrinkage and anisotropy of the material, thereby reducing the linear expansion coefficient and warpage.

[0031] As can be seen from Examples 4, 5 and Comparative Example 2, the introduction of HPBSi and high-flow PS can significantly improve the flowability of the material. HPBSi contributes more to the flowability and has a lower impact on the heat distortion temperature of the material. The combination of the two materials provides the possibility for thin-wall injection molding. Although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

[0032] Therefore, the above description is only a preferred embodiment of this application and is not intended to limit the scope of this application; that is, all equivalent modifications made in accordance with the scope of the claims of this application shall be within the protection scope of the claims of this application.

Claims

1. A PPE / PPS composition, characterized in that, It is prepared from the following components in weight percentage: PPE resin 35-45% PPS resin 20-30% 15-30% glass fiber Inorganic fillers 2-15% Compatibilizer 1-5% Flowability improver 2-10% Other adjuvants: 0.6-1.5%.

2. The PPE / PPS composition according to claim 1, characterized in that, The PPE resin has a melt flow rate of 10-50 g / 10 min at 315°C and 10 kg; and / or, the PPS resin has a melt flow rate of 1000-1200 g / 10 min at 316°C and 5 kg; and / or, the compatibilizer has a melt flow rate of 7-20 g / 10 min at 190°C and 2.16 kg.

3. The PPE / PPS composition according to claim 1, characterized in that, The glass fiber is a flat glass fiber with a cross-sectional length-to-minor axis ratio of 3-5:

1.

4. The PPE / PPS composition according to claim 1, characterized in that, The inorganic filler is at least one of mica and wollastonite; the mica is flaky mica with an aspect ratio of 50-120 and an average flake diameter of 10-40 μm; the wollastonite is acicular wollastonite with an aspect ratio of 2-8 and a fiber diameter of 10-30 μm.

5. The PPE / PPS composition according to claim 1, characterized in that, The compatibilizer is a copolymer of styrene and methacrylate.

6. The PPE / PPS composition according to claim 1, characterized in that, The flowability improver is at least one of high-flow polystyrene and hyperbranched polyester-polysiloxane block copolymer.

7. The PPE / PPS composition according to claim 1, characterized in that, The other additives are at least one of lubricants, coupling agents, and antioxidants; And / or, the lubricant is at least one of pentaerythritol tetrastearate, silicone powder, or a mixture thereof; And / or, the coupling agent is γ-aminopropyltriethoxysilane; And / or, the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1 to 1:

2.

8. The method for preparing the PPE / PPS composition according to any one of claims 1-7, characterized in that, Includes the following steps: All components except glass fiber are mixed evenly to obtain a mixture; The mixture is added to the main feed port of a twin-screw extruder, and glass fibers are added to the side feed port of the twin-screw extruder. After melting, extrusion, and granulation, a PPE / PPS composition is obtained.

9. The preparation method according to claim 8, characterized in that, The extruder has the following temperature zones: Zone 1: 100–200℃; Zone 2: 260–300℃; Zone 3: 260–320℃; Zone 4: 260–320℃; Zone 5: 260–320℃; Zone 6: 260–320℃; Zone 7: 260–320℃; Zone 8: 260–320℃; Zone 9: 260–320℃; Zone 10: 260–320℃; Die head temperature: 270–320℃; Screw speed: 300–700 rpm.

10. The application of the PPE / PPS composition according to any one of claims 1-7 in 5G communications, new energy vehicles, precision electronics, millimeter-wave radar, power batteries and ultra-thin-wall injection molded parts.

Citation Information

Patent Citations

  • Polyphenyl ether / high impact polystyrene composition with low linear expansion coefficient and preparation method thereof

    CN111995859A

  • Heat-conducting ultralow-linear-expansion-coefficient PPS composite material for plastic cavity filter and preparation method thereof

    CN116120747A

  • Platable Poly(Phenylene Sulfide) and Poly(Phenylene Ether) Compositions

    US20240218179A1

Cited By

  • Junction box material and preparation method thereof

    CN121554939A